(untitled) (Research, Society and Development, 2024)
Gestational Diabetes Mellitus (GDM) is a condition in the spectrum of hyperglycemia during pregnancy resulting from physiological changes during pregnancy in a predisposed mother. This condition has serious consequences for the mother-fetus binomial, such as preeclampsia and prematurity, which points to the importance of management. This study aimed to elucidate the aspects of screening, diagnosis, and non-pharmacological treatment of Gestational Diabetes Mellitus through a review of the existing literature, using original articles and books published between 2015 and 2024, in English, German, and Portuguese. The search was carried out in the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (Scielo), Google Scholar, Virtual Health Library (VHL), and EBSCO Information Services databases, between September and October 2024, using the keywords: “Gestational Diabetes”, “screening”, “diagnosis”, and “diet therapy”. After selection and critical reading, 25 studies were included in the review. It was observed that screening and diagnosis vary in terms of criteria and indications at the international level. In Brazil, there is a structured recommendation to carry out universal screening in order to identify pregnant women with hyperglycemia from the first prenatal visit. With regard to non-pharmacological treatment, nutritional therapy, physical activity and glycemic monitoring are recommended. This study contributes to the literature by promoting the formatting of concepts related to Gestational Diabetes Mellitus (GDM), in terms of screening, diagnosis and non-pharmacological treatment.